Development and a Validation of a Charge Sensitive Organic Rankine Cycle (ORC) Simulation Tool - Davide Ziviani; Brandon J. Woodland; Emeline Georges; Eckhard A. Groll; James E. Braun; W. Travis Horton; Martijn van den Broek; Michel De Paepe (Energies, 2016)
Despite the increasing interest in organic Rankine cycle (ORC) systems and the large number of cycle models proposed in the literature, charge-based ORC models are still almost absent. In this paper, a detailed overall ORC simulation model is presented based on two solution strategies: condenser subcooling and total working fluid charge of the system. The latter allows the subcooling level to be predicted rather than specified as an input. The overall cycle model is composed of independent models for pump, expander, line sets, liquid receiver and heat exchangers. Empirical and semi-empirical models are adopted for the pump and expander, respectively. A generalized steady-state moving boundary method is used to model the heat exchangers. The line sets and liquid receiver are used to better estimate the total charge of the system and pressure drops. Finally, the individual components are connected to form a cycle model in an object-oriented fashion. The solution algorithm includes a preconditioner to guess reasonable values for the evaporating and condensing temperatures and a main cycle solver loop which drives to zero a set of residuals to ensure the convergence of the solution. The model has been developed in the Python programming language. A thorough validation is then carried out against experimental data obtained from two test setups having different nominal size, working fluids and individual components: (i) a regenerative ORC with a 5 kW scroll expander and an oil flooding loop; (ii) a regenerative ORC with a 11 kW single-screw expander. The computer code is made available through open-source dissemination.